Closer to godliness: a contextual study of osteoarchaeological and spatial patterns of diseased individuals in medieval Danish cemeteries - Kelmelis, Saige; Kristensen, Vicki Rytoft; Larsen, Lars Agersnap; Knudsen, Maria; Mollerup, Lene; Seeberg, Lone; Pedersen, Dorthe Dangvard (Frontiers in Environmental Archaeology, 2026)
IntroductionMedieval Danish populations (c. 1050-1536 AD) faced numerous infectious diseases, including leprosy and tuberculosis, that shaped modern perceptions of medieval health crises. While previous studies explored disease spread and mitigating factors like leprosaria, it remains unclear how health status influenced burial treatment and placement within church cemeteries. Cemetery analyses may also clarify whether urban-rural mortality differences were affected by proximity to care institutions. This study integrates paleoepidemiology and spatial archaeology to examine health and death treatments in 939 adults from three urban and two rural medieval Danish collections.MethodsBone involving disease prevalence was estimated using probabilistic estimates of sensitivity and specificity from skeletal indicators of leprosy and tuberculosis, enabling spatial comparisons of infected and non-infected individuals across cemeteries. Differential survivorship and mortality hazards were evaluated using Kaplan-Meier and Cox regression analyses.ResultsResults showed no distinct patterns of clustering of skeletons with positive disease states that suggest specific treatment of disease sufferers in death, but notable variation was found in burial status distribution and survivorship between cemeteries with high status individuals having lower mortality. No significant survivorship differences existed between those with and without leprosy, whereas tuberculosis-positive individuals had significantly higher survivorship than non-lesioned peers (p < 0.001).DiscussionThe absence of leprosy sufferers in urban cemeteries reinforces leprosaria's selective effect on burial placement, while tuberculosis prevalence was high across all cemeteries, indicating no differential treatment. This study demonstrates medieval Danes' complex relationship with disease, status, and burial practices.